2015
DOI: 10.1038/sc.2015.210
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of neuropathic pain and its relationship with quality of life in 72 patients with spinal cord injury

Abstract: Study design: A cross-sectional study. Objectives: Neuropathic pain (NP) after spinal cord injury (SCI) tends to be hard to treat, and its heterogeneous properties make it difficult to identify and characterize. This study was conducted to assess the characteristics of SCI-related NP in detail. Setting: A single hospital for SCI rehabilitation. Methods: This study included 72 patients who were seen at our hospital in 2012 and 2013 and who had sustained SCI at least 3 months before enrollment. The patients comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 25 publications
(38 reference statements)
1
25
0
Order By: Relevance
“…A previous study reported that individuals with an AIS grade of B experienced more intense NP than those with other grades (9). A relationship between completeness of injury and prevalence of pain was also reported previously (21).…”
Section: Pain Variables As Predictors Of Craig Handicap Assessment Resupporting
confidence: 66%
See 2 more Smart Citations
“…A previous study reported that individuals with an AIS grade of B experienced more intense NP than those with other grades (9). A relationship between completeness of injury and prevalence of pain was also reported previously (21).…”
Section: Pain Variables As Predictors Of Craig Handicap Assessment Resupporting
confidence: 66%
“…Pain takes a toll on an individual's activity levels and mental health status, reducing their quality of life (QoL). Chronic pain is associated with poorer psychological functioning and lower QoL (7)(8)(9)(10). Social integration is an important factor for health-related QoL after critical illness (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Transport 155 (40) 64 (44) 93 (40) 126 (42) 158 (42) 61 (39) Fall 124 (32) 37 (25) 69 (30) 92 (31) 107 2853 (34) Other traumatic cause 48 (12) 16 (11) 33 1431 1045 1220 (13) Employment (full or part time), yes, n (%) 34 (15) 72 2454 1452 (34) Moderate 142 (37) 44 (30) 87 (38) 99 (33) 135 3651 (33) Much 185 (48) 40 (27) 110 (47) 115 (38) 184 4842 (27) Quality of life, NRS (0-10), mean (s. reported treatment for spasticity. Baclofen was the most frequently used medication for spasticity used by 40% (35% oral and 5% pump) of those with spasticity ( Figure 1).…”
Section: Spasticitymentioning
confidence: 99%
“…8,9 Chronic pain is associated with poorer psychological functioning and lower quality of life, 8,[10][11][12][13][14] but few studies have looked into the role of specific pain types on quality of life. 15,16 Spasticity is another common complication present in about 70% of all SCI after the first year. 17 Spasticity is a broad term that includes velocity-dependent increase in muscle tone, enhanced tendon reflexes, muscle spasms and clonus.…”
Section: Introductionmentioning
confidence: 99%